Analysis of cochannel interference in multi-cell OFDM networks - Chi-Hsiao Yih; Geraniotis, E. (Ninth IEEE International Symposium on Personal, Indoor, and Mobile Radio Communications : technical program proceedings, September 8-11, 1998, the Marriott Copely Place, Boston, Massachusetts, 1998)
This paper provides an analytical framework for evaluating the performance of multi-cell orthogonal frequency division multiplexing (OFDM) networks in the presence of cochannel interference (CCI), frequency selective Rayleigh fading and additive white Gaussian noise (AWGN). Coherent and differential coherent modulation methods along with the imperfect power control mechanisms are considered in our analysis and the corresponding formulas of symbol error rate (SER) are derived. Moreover, forward error control coding schemes using bandwidth efficient inner trellis codes and outer Reed-Solomon codes are employed to improve system performance. The expressions of the asymptotic bit error rate (BER) of the inner trellis code and the SER of the concatenated code are analyzed. Finally, numerical results verify the effectiveness of the concatenated coding scheme in combating the channel fading and cochannel interference in OFDM networks.